KUALITAS HIDUP LANJUT USIA YANG TINGGAL DI PANTI: STUDI LITERATUR - Kowureng, Majesty; Kairupan, Kairupan; Kristamuliana, Ns. (Universitas Sam Ratulangi, 2020)
Abstract : The increasing elderly population is a global phenomenon nowadays. Faced with this, the importance of ensuring the elderly is not only seen from a long life but also the quality of life of the elderly needs to be considered. Objective. The purpose of this literature study is to explain the quality of life and strategies to improve the quality of life of the elderly who live in nursing homes. Method. The method used to compile this literature study is by searching through an electronic database. Searching for articles is done by using the keywords Quality Of Life, Elderly, Nursing Homes, that are traced through Google Scholar, Pubmed, and Science Direct. The Joanna Briggs Institute (JBI) Critical Appraisal is used to assess and analyze the quality of the article methodology. Result. There were 723 articles published from 2015 to 2019 related to the quality of life of elderly living in nursing homes that were identified. However, of 723 articles, only 6 articles met with the review requirements. Six articles that meet the inclusion criteria are divided into two major themes, namely the quality of life of elderly living in nursing homes (4 studies) and interventions that affect improving the quality of life of elderly living in nursing homes (2 studies). Conclusion. This literature study concludes that the majority of elderly people living in nursing homes had a moderate quality of life and physical activity interventions and religious-spiritual interventions affected improving the quality of life in elderly nursing homes. Suggestion. The author suggests making modifications to the nursing care of the elderly who live in nursing homes that are adjusted to any changes that occur in the elderly needed to improve their quality of life.Keywords : Quality of Life, Elderly, Nursing Homes.Â Abstrak: Peningkatan populasi lanjut usia merupakan fenomena global saat ini. Menghadapi hal tersebut, pentingnya menjamin lanjut usia bukan hanya dilihat dari umur yang panjang, tetapi juga kualitas hidup lanjut usia perlu untuk diperhatikan. Tujuan penelitian ini untuk menjelaskan kualitas hidup dan strategi peningkatan kualitas hidup lanjut usia yang tinggal di panti. Metode yang digunakan untuk menyusun studi literatur ini adalah dengan mencari melalui database elektronik. Pencarian artikel dilakukan dengan menggunakan kata kunci Quality Of Life, Elderly, Nursing Homes, yang ditelusuri melalui Google Scholar, Pubmed, dan Science Direct. Menilai dan menganalisis kualitas metodologi dalam setiap studi menggunakan The Joanna Briggs Institute (JBI) Critical Appraisal. Hasil. Didapatkan 723 artikel terkait kualitas hidup lanjut usia yang tinggal di panti yang diidentifikasi dan dipublikasikan dari tahun 2015-2019. Dari 723 artikel hanya 6 artikel yang memenuhi syarat untuk dianalisis. Enam artikel yang memenuhi kriteria inklusi terbagi menjadi dua tema besar yaitu kualitas hidup lanjut usia yang tinggal di panti (4 studi) dan intervensi yang berpengaruh meningkatkan kualitas hidup lanjut usia yang tinggal di panti (2 studi). Kesimpulan. Dari studi literatur ini dapat disimpulkan bahwa sebagian besar lanjut usia yang tinggal di panti memiliki kualitas hidup pada tingkat sedang dan intervensi aktivitas fisik dan intervensi spiritual keagamaan berpengaruh pada peningkatan kualitas hidup lanjut usia yang tinggal di panti. Saran. Melakukan modifikasi pada asuhan keperawatan lanjut usia yang tinggal di panti yang disesuaikan dengan setiap perubahan yang terjadi pada lanjut usia sangat diperlukan demi meningkatkan kualitas hidup mereka.